Harvesting condensate into potable water - Rekha Y, Andal V , Suriya S, (International Journal of Advanced Science and Technology, 2020)
Globally, the population growth and urbanization has increased the air conditioning unit installation. The air conditioner lowers the temperature and allows the moisture to condense and the condensate is obtained. Conserving the condensate is sustainable development for water resources. In the current paper the condensate from air conditioner was analyzed, discussed and reclaimed into potable water. Water was collected from residential houses which include individual houses, apartments having 8 number of flats and a gated community with 250 number of houses. The physicochemical value and biological results of condensate was within Indian Standard (BIS). Thus the water can be made suitable for potable by adopting a microfiltration and disinfection treatment. A cost effective device was fabricated to convert condensate water into potable water, which can be a better substitute during water crisis and it would be an effective harvesting technology.